Efektivitas Surface-flow Wetlands untuk Reduksi Polutan Organik pada Air Limbah Domestik dengan Kayu Apu (Pistia stratiotes L.) - Anggrika Riyanti; Hadrah Hadrah; Marhadi Marhadi; Emelda Raudhati; Iptahul Jannah (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The treatment of domestic wastewater in communal systems currently faces many challenges, including a decline in treatment performance due to the high pollutant load entering the system, resulting from inadequate maintenance. Therefore, a system is needed to support the optimal performance of wastewater treatment plants (WWTPs), namely surface-flow wetlands (SF-Wetlands). This study aims to analyze the effect of retention time on the effectiveness of organic matter removal in surface-flow wetlands using Pistia stratiotes L. plants. The retention times used were 12, 24, 36, 48, 60, and 72 hours. The domestic wastewater parameters analyzed were BOD5 and ammonia. The results showed that the highest efficiency in reducing BOD5 concentration occurred at a retention time of 72 hours, with a reduction of 97.42% to 16.85 mg/L, while ammonia was reduced by 82.43% to 3.86 mg/L. The values achieved met the quality standards of PermenLHK Number 16 of 2016. Retention time significantly affects the removal of organic matter from domestic wastewater. An increase in retention time is needed to improve ammonia removal in the SF-wetlands system.